PRAKTIK GHARAR DAN MAISIR ERA MODERN - Tuah Itona Tona (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2022)
Along with the development of technology in this modern era, it also develops in terms of muamalah transactions such as the presence of new applications that change contracts that were previously carried out in person can now be done online and are considered to be easier, the sophistication of the technology can also have an impact on transactions that contain elements of fraud, betting and others by irresponsible parties. In modern muamalah activities, there are gharar and maysir practices carried out by several parties. The presence of sophisticated transactions in this modern era makes users not aware of whether the transaction contains elements such as gharar (obscurity) and maisir (gambling) in the device or transaction. The prohibition of gharar and maysir is increasingly relevant for this modern era because modern markets contain many attempts to transfer risk (danger) to other parties that contain elements of gambling. Because this transaction is prohibited in Islam and as economic actors, humans must be more careful and selective in order to avoid gharar and maysir which in this modern era have turned into several forms such as in banking, insurance, stock exchanges, online gambling and games online.